Optimal haemodynamics during left ventricular assist device support are associated with reduced haemocompatibility‐related adverse events. (28th December 2018) - Imamura, Teruhiko; Nguyen, Ann; Kim, Gene; Raikhelkar, Jayant; Sarswat, Nitasha; Kalantari, Sara; Smith, Bryan; Juricek, Colleen; Rodgers, Daniel; Ota, Takeyoshi; Song, Tae; Jeevanandam, Valluvan; et al.
Abstract : Aims: Left ventricular assist device (LVAD) therapy improves the haemodynamics of advanced heart failure patients. However, it is unknown whether haemodynamic optimization improves haemocompatibility‐related adverse events (HRAEs). This study aimed to assess HRAEs in patients with optimized haemodynamics. Methods and results: Eighty‐three outpatients [aged 61 (53–67) years, 50 male] underwent a haemodynamic ramp test at 253 (95–652) days after LVAD implantation, and 51 (61%) had optimized haemodynamics (defined as central venous pressure < 12 mmHg, pulmonary artery wedge pressure < 18 mmHg, cardiac index > 2.2 L/min/m 2 ) following LVAD speed adjustment. One‐year survival free of any HRAEs (non‐surgical bleeding, thromboembolic event, pump thrombosis, or neurological event) was achieved in 75% of the optimized group and in 44% of the non‐optimized group (hazard ratio 0.36, 95% confidence interval 0.18–0.73, P  = 0.003). The net haemocompatibility score, using four escalating tiers of hierarchal severity to derive a total score for events, was significantly lower in the optimized group than the non‐optimized group (1.02 vs. 2.00 points/patient; incidence rate ratio 0.51, 95% confidence interval 0.29–0.90, P  = 0.021). Conclusion: Left ventricular assist device patients in whom haemodynamics can be optimized had greater freedom from HRAEs compared to those without optimized haemodynamics.